2020
DOI: 10.1039/c9nj05867b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral activity of novel myricetin derivatives containing ferulic acid amide scaffolds

Abstract: A variety of myricetin derivatives bearing ferulic acid amide scaffolds were designed and synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 28 publications
0
29
0
2
Order By: Relevance
“…Based on the previously reported method [36][37][38], the synthetic route of target compound is listed in Scheme 1. The myricetin, anhydrous potassium carbonate and N,Ndimethylformamide (DMF) were added to a round-bottom flask with magnetic stirring; the reaction mixture was allowed to stir for 20 min at room temperature and potassium iodide was asses dropwise slowly.…”
Section: General Synthesis Procedures For Intermediate 1 and Intermedimentioning
confidence: 99%
“…Based on the previously reported method [36][37][38], the synthetic route of target compound is listed in Scheme 1. The myricetin, anhydrous potassium carbonate and N,Ndimethylformamide (DMF) were added to a round-bottom flask with magnetic stirring; the reaction mixture was allowed to stir for 20 min at room temperature and potassium iodide was asses dropwise slowly.…”
Section: General Synthesis Procedures For Intermediate 1 and Intermedimentioning
confidence: 99%
“…trans-Ferulic acid derivatives containing acylhydrazone moiety also showed activity against tobacco mosaic virus [28] . Novel myricetin derivatives containing ferulic acid amide scaffolds were also found to be active against tobacco mosaic virus [29] . It appears that other compounds conjugated with ferulic acid may have antiviral activities.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the excellent features of low toxicity, the fact that it is easily synthetized and derived, and considering pyrimidine as a parent compound, the development of promising agrochemical candidates will soon become a reality. Meanwhile, amine, a key moiety in heterocyclic chemistry, play a leading role in pesticide chemistry due to their potent bioactivities including antifungal ( Cheng et al, 2020 ; Chen et al, 2021a ), antibacterial ( Chen et al, 2021a ), antiviral ( Tang et al, 2020 ), herbicidal ( Sun et al, 2020 ), and insecticidal ( Chen et al, 2021b ; Li et al, 2021b ) activities. In our previous work, we reported a series of novel pyrimidine derivatives containing an amine moiety ( Figure 1 ) and found that the target compounds revealed certain antifungal, insecticidal, and antiviral activities ( Wu et al, 2016a : Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%